Relationship between Body Mass Index and Anemia in Adolescent Girls at Madrasah Aliyah Nurul Islam - Arsy, Lazuardi; Cholidah, Rifana; Ayunda, Rahmah Dara (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Indonesia, 4 out of 10 teenagers suffer from anemia. Adolescent girls have a higher likelihood of experiencing anemia due to physical and psychological changes that affect greater nutritional needs. Some references associate anemia with differences in body mass index, thus further research is needed on the relationship between body mass index and the occurrence of anemia. This study aims to determine the relationship between Body Mass Index and the occurrence of Anemia in adolescent girls at MA Nurul Islam. The research design used in this study is cross-sectional. The population consisted of adolescent girls aged 15-18 years from MA Nurul Islam who had started menstruating. The study employed consecutive sampling technique, involving a total of 46 participants. The chi-square test results indicate no association between body mass index and the occurrence of anemia (p = 1.000; PR = 0.800; 95% CI = 0.178-3.587). Additionally, other characteristics such as menstrual duration, menstrual cycle, iron supplement consumption, and parental income also did not show significant associations with the occurrence of anemia among adolescent girls at MA Nurul Islam in this study. This study found no association between body mass index (BMI) and the incidence of anemia in adolescent girls at MA Nurul Islam. Other characteristics examined, such as menstrual duration, menstrual cycle, iron supplement consumption, and parental income, also did not show significant associations with the occurrence of anemia. Therefore, further research with different approaches is needed to evaluate other factors that may affect anemia in adolescent girls.